2020
DOI: 10.3390/molecules25163639
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Pharmaceuticals from Water by Free and Imobilised Microalgae

Abstract: Pharmaceuticals and their metabolites are released into the environment by domestic, hospital, and pharmaceutical industry wastewaters. Conventional wastewater treatment technology does not guarantee effluents of high quality, and apparently clean water may be loaded with pollutants. In this study, we assess the performance and efficiency of free and immobilised cells of microalgae Nannochloropsis sp. in removing four pharmaceuticals, chosen for their occurrence or persistence in the environment. These are par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…This approach can be used as a preliminary step before being subjected to advanced reported techniques to improve removal efficiency. Several authors reported on a new methodology to remove pharmaceutical contaminants from wastewater, such as (a) triboelectric generator, (b) microalgae, (c) nanofiltration membrane bioreactor, (d) polymeric coating, and (e) piezoelectric electrospun nanofiber membrane [ 19 , 20 , 21 , 22 , 23 ]. Khushwaha et al developed a triboelectric generator as an efficient and green approach (80% degradation efficiency achieved using the triboelectric effect) to treat wastewater [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach can be used as a preliminary step before being subjected to advanced reported techniques to improve removal efficiency. Several authors reported on a new methodology to remove pharmaceutical contaminants from wastewater, such as (a) triboelectric generator, (b) microalgae, (c) nanofiltration membrane bioreactor, (d) polymeric coating, and (e) piezoelectric electrospun nanofiber membrane [ 19 , 20 , 21 , 22 , 23 ]. Khushwaha et al developed a triboelectric generator as an efficient and green approach (80% degradation efficiency achieved using the triboelectric effect) to treat wastewater [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several GNEs (water in oil) were prepared using water, DMSOT (DMSO containing constant amount of transcutol, 10% v / v ), isopropyl alcohol (IPA), and CMC8, as per the reported method [ 20 , 35 ]. Several batches of green nanoemulsions were prepared using the oil phase titration method [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…etc., as described by [28]. Afterward, a certain amount (20 × 10 6 cell mL −1 ) of marine diatom [29] was transferred to a 6 L (a lab-scale) bubble column photobioreactor at room temperature under white fluorescent light illumination (66 µmol photonsm −2 s −1 ) (González-González et al [30]). The photobioreactor was a tank (width (7 cm), length (20 cm), and height (44 cm)) that had a working value of 6 L. The aeration was done from the bottom.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the agrochemicals’ highly negative impacts, its removal from soil and water is a major challenge [ 10 , 11 ]. Hence, the improvement of environmental remediation techniques [ 12 ], e.g., biological treatment [ 13 ] and advanced oxidation processes [ 14 ], is pivotal. Sorption processes and materials have wakened great attention being straightforward in application and often reusable, showing good efficiency and advantageous cost effectiveness.…”
Section: Introductionmentioning
confidence: 99%